Inclusion of deaf people in industry: Lessons learned from the usability evaluation of AppTalk - Holanda, Saymon Farias; Virginia, Larah; Monteiro, Ingrid (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Accessibility for deaf people, especially in the workplace, is a continuous process that requires the active participation of deaf users and constant search for improvements. Knowing their needs and experiences is a key point to ensuring that digital systems and applications are truly inclusive. In this context, the AppTalk was developed, which is an application whose objective is to make the transmission of information more accessible in the manufacturing environment of the company Dell Technologies, through the communication in Libras between a 3D avatar and the deaf user. This paper describes part of the development of the AppTalk current version for web and also its usability evaluation, using the System Usability Scale (SUS) in conjunction with a usability test. To ensure the effectiveness of the system, the team adopted user-centered approaches and involved deaf people and Libras interpreters in all phases of the project. User research were conducted to understand the needs and preferences of Dell’s deaf employees, taking into account factors such as communication, interaction and accessibility. This paper is an experience report that highlights the challenges and lessons learned from the usability test and the application of SUS as methods of AppTalk usability evaluation. The results obtained can serve as a basis for future improvements and research related to the development of accessible technologies for people with hearing impairment.